SOCIOLOGICAL PROPERTIES OF SLANG USED BY THE CHARACTERS IN STEP UP 2 THE STREETS MOVIE - Meinawati, Euis; Dewi, Nurmala; Rachmawati, Dina (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
The objective of this research is to know the function of the usage of slang, especially slang used by the characters of Step Up 2 The Streets movie. The method of this research used descriptive qualitative method, the data were collected through observation of the movie, analysis of slang in the dialogue, and analysis sociological properties of slang based on the dialogues. Defining the sociological properties of slang and analyzing the most frequent of properties used are taken from the theory of Mattiello. Analyzing the purposes of using slang in a community is taken from the theory of Victor and Dalzel. The result of this research are: (1) From 31 sociological properties are known, only 14 properties used in the movie, following: ‘Color’, ‘Efficiency’, ‘Group-Restriction’, ‘Informality’, ‘Subject-Restriction’, ‘Orality’, ‘Musicality’, ‘Aggressiveness’, ‘Unconventionality’, ‘Offenciveness’ ‘Desire to Impress’, ’Hybridism’, ‘Localism’, ‘Secrecy’, (2) The most frequent of sociological properties is ‘colour’, (3) The purposes of using slang are: to enrich the language, to induce friendliness or intimacy, to prove that someone did not belong to a certain society, and to be secret.